Force Analysis for Three Ring Reductor - 崔建昆; 张光辉 (Jixie chuandong)
In this paper,A force analysis mode have been set up for the double cranks mechanism with virtual constraints by means of stractural deformation coordination equations of the kinematic pairs,The way by which a multiphase concatenation double cranks mechanism overcome its fixed point in the three ring reductor are discussed.The load of planetary bearings and the moment in the high speed shafts are analyzed and some suggestions about the structure type and design parameters of the three ring reductor were also presented